2016
DOI: 10.1044/2016_jslhr-l-15-0005
|View full text |Cite
|
Sign up to set email alerts
|

Joint Engagement and Early Language in Young Children With Fragile X Syndrome

Abstract: Purpose: In this study, we examine joint engagement (JE) in young children with fragile X syndrome (FXS) and its relationship to language abilities and autism spectrum disorder symptomatology at 24 to 36 months (toddler period) and 59 to 68 months (child period). Method: Participants were 28 children with FXS (24 boys, four girls) and their mothers. Videotaped home observations were conducted during the toddler period and coded for JE. Language abilities were measured at both ages from a developmental assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Therefore, the presence of autism spectrum disorder will also have a cascading effect on early social development in neurogenetic disorders. For example, higher levels of autism spectrum disorder symptomatology have been consistently related to more impaired functioning in FXS (Bailey, Hatton, Skinner, & Mesibov, 2001; Hahn, Brady, Warren, & Fleming, 2015; Roberts, Mankowski, et al, 2009), and this pattern has also been observed in early social development (Flenthrope & Brady, 2010; Hahn et al, 2016). Similarly, a study examining the presence of autism spectrum disorder in DS indicates that potential early indicators include impairments in social and communication skills (Hepburn, Philofsky, Fidler, & Rogers, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the presence of autism spectrum disorder will also have a cascading effect on early social development in neurogenetic disorders. For example, higher levels of autism spectrum disorder symptomatology have been consistently related to more impaired functioning in FXS (Bailey, Hatton, Skinner, & Mesibov, 2001; Hahn, Brady, Warren, & Fleming, 2015; Roberts, Mankowski, et al, 2009), and this pattern has also been observed in early social development (Flenthrope & Brady, 2010; Hahn et al, 2016). Similarly, a study examining the presence of autism spectrum disorder in DS indicates that potential early indicators include impairments in social and communication skills (Hepburn, Philofsky, Fidler, & Rogers, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, observational studies of young children with FXS suggest that joint attention and joint engagement are commensurate with developmental level (Hahn et al, 2016; Roberts et al, 2002). Also during social interactions, it seems that young children with FXS are particularly skilled at using eye gaze shifts for the purpose of sharing interests, making requests, and commenting (Roberts et al, 2002), despite the extant research on children, adolescents, and adults with FXS that reports impairments in eye gaze, especially for social purposes (Cohen et al, 1988; Hall et al, 2015; Hessl, Glaser, Dyer-Friedman, & Reiss, 2006; Murphy et al, 2007; Wolff et al, 1989).…”
Section: Early Social Development In Neurogenetic Disordersmentioning
confidence: 94%
See 1 more Smart Citation
“…Impairments in joint attention, a social referencing skill [ 47 ] that is a core precursor to social cognition and social interaction skills and behaviours [ 48 , 49 ], may also contribute to the break in performance. Whilst participants can pass the two easiest ESCogS tasks by making inferences based on the examiner’s actions, the next four tasks require participants to either respond to the examiner’s use of joint attention, by indicating which box a toy is hidden in (both Gestures tasks) or initiate joint attention by directing the examiner’s attention so that they can fulfil their role in completing a joint goal (both Cooperation tasks).…”
Section: Discussionmentioning
confidence: 99%
“…Each behavior-child engagement state, child gesture, maternal gesture-is coded within one observation file in separate passes to ensure that no behaviors are missed, while allowing all behaviors to be viewed together (see Table 2 for definitions and examples). Child engagement is coded using the procedures and coding scheme of Hahn and colleagues 74 based on the work of Adamson and colleagues. 75,76 In this coding scheme, codes are based on the engagement of the child during a naturalistic interaction (free play).…”
Section: Engagement State and Gesture Codingmentioning
confidence: 99%